2019
DOI: 10.1155/2019/9840890
|View full text |Cite
|
Sign up to set email alerts
|

IgE, IgG1, and IgG4 Reactivity toDermatophagoides pteronyssinusGlycosylated Extract in Allergic Patients

Abstract: Background. House dust mites are important allergen sources and some of these allergenic proteins may contain carbohydrate moieties, which are able to be isolated using lectins, as Concanavalin A (ConA). This study aimed to investigate allergenicity (IgE) and antigenicity (IgG1 and IgG4) of ConA-unbound and ConA-bound Dermatophagoides pteronyssinus (Dpt) crude extracts using sera of mite-allergic patients as well as inhibition capacity of antibody binding. Material and Methods. We obtained mannose-enriched and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…To evaluate the inhibition of S2 against extract S1, competitive inhibition ELISA was conducted as previously described ( 23 ). High-affinity microtiter plates were loaded with extract S1 (1 μg/well) in carbonate-bicarbonate buffer, and plates were then blocked with PBS-T containing 1% BSA for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the inhibition of S2 against extract S1, competitive inhibition ELISA was conducted as previously described ( 23 ). High-affinity microtiter plates were loaded with extract S1 (1 μg/well) in carbonate-bicarbonate buffer, and plates were then blocked with PBS-T containing 1% BSA for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…A wheal diameter ≥ 3 mm after 15 min was considered positive. Serum samples were used to detect D. farinae-specific IgE by an indirect ELISA [30]. Briefly, high-affinity microplates were coated with 40 µg/mL D. farinae extract for 18 h at 4 • C and blocked with phosphate-buffered saline/0.05% Tween (PBS-T) with 1% Bovine Serum Albumin (BSA).…”
Section: Spt With Airborne Allergens and D Farinae-specific Ige Elisamentioning
confidence: 99%
“…Dermatophagoides pteronyssinus (DP), a widely popular dominant house dust mite (HDM) which generally known as strong inducers of IgE antibody response (Liao et al 2015), has been identified to have many IgE-binding components in the allergen extract (Resende et al 2019). Allergy is mainly caused by Der p 1 and Der p 2 allergens and these allergens are recognized by more than 80% of atopic individuals (Cui et al 2018).…”
Section: Introductionmentioning
confidence: 99%